MR-based quantitative measurement of human soft tissue internal strains for pressure ulcer prevention. (October 2022) - Trebbi, Alessio; Mukhina, Ekaterina; Rohan, Pierre-Yves; Connesson, Nathanaël; Bailet, Mathieu; Perrier, Antoine; Payan, Yohan
Highlights: Image registration from unloaded and loaded MR images can be used to calculate soft tissue internal strains. Image quality has an impact in the reproducibility of strain calculation through image registration. Artificially deformed images can be used to quantify the trueness of strain calculation from image registration. Image registration is a tool that can be used to define, compare and validate finite element simulations. Abstract: Pressure ulcers are a severe disease affecting patients that are bedridden or in a wheelchair bound for long periods of time. These wounds can develop in the deep layers of the skin of specific parts of the body, mostly on heels or sacrum, making them hard to detect in their early stages. Strain levels have been identified as a direct danger indicator for triggering pressure ulcers. Prevention could be possible with the implementation of subject-specific Finite Element (FE) models. However, generation and validation of such FE models is a complex task, and the current implemented techniques offer only a partial solution of the entire problem considering only external displacements and pressures, or cadaveric samples. In this paper, we propose an in vivo solution based on the 3D non-rigid registration between two Magnetic Resonance (MR) images, one in an unloaded configuration and the other deformed by means of a plate or an indenter. From the results of the image registration, the displacement field and subsequent strain maps for the soft tissues were computed. An extensive study, considering different cases (on heel pad and sacrum regions) was performed to evaluate the reproducibility and accuracy of the results obtained with this methodology. The implemented technique can give insight for several applications. It adds a useful tool for better understanding the propagation of deformations in the heel soft tissues that could generate pressure ulcers. This methodology can be used to obtain data on the material properties of the soft tissues to define constitutive laws for FE simulations and finally it offers a promising technique for validating FE models.